An oxidation mechanism map for tungsten. (1st March 2022) - Nagy, Dóra; Humphry-Baker, Samuel A.
Abstract: A tungsten oxidation mechanism map is developed to clarify literature confusion about the dominant oxidation kinetic regime and to enable improved predictions in extreme environments. Thermogravimetry data is systematically extracted from 14 papers in the range 600–1600 °C and treated as three distinct kinetic regimes: parabolic oxidation, linear oxidation, and sublimation. A mechanism map is constructed that shows metal recession thickness contours for each regime in time-temperature space. The map enables consideration of a fusion reactor accident combining loss of coolant and vacuum, in which a tungsten first wall could reach ∼1200 °C for several weeks. Complete oxidation of the first wall and 2 mm of sublimation is predicted. Similar maps must be developed for accident tolerant tungsten alloys if reliable predictions are to be made about their performance. Graphical abstract: Image, graphical abstract